2012
DOI: 10.1038/ncomms1689
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ferromagnetism in Teflon due to carbon dangling bonds

Abstract: The ferromagnetism in many carbon nanostructures is attributed to carbon dangling bonds or vacancies. This provides opportunities to develop new functional materials, such as molecular and polymeric ferromagnets and organic spintronic materials, without magnetic elements (for example, 3d and 4f metals). Here we report the observation of room temperature ferromagnetism in Teflon tape (polytetrafluoroethylene) subjected to simple mechanical stretching, cutting or heating. First-principles calculations indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 30 publications
3
44
1
Order By: Relevance
“…22 Defects, as active sites where the charge carriers can be effectively separated, 23,24 have been recently reported to narrow the band gap as well. 25 Thus, the defect bismuth oxy-hybrid-halides have the potential to reconcile the apparent contradiction between bandgap narrowing and performance, and to provide an ideal platform to attain a comprehensive understanding of correlations between the structure, defects, and properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 Defects, as active sites where the charge carriers can be effectively separated, 23,24 have been recently reported to narrow the band gap as well. 25 Thus, the defect bismuth oxy-hybrid-halides have the potential to reconcile the apparent contradiction between bandgap narrowing and performance, and to provide an ideal platform to attain a comprehensive understanding of correlations between the structure, defects, and properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Vacancy mediated magnetism occurs in CuO [17] and ZnO [18,19]; oxygen vacancy induced magnetism in zinc peroxide [20] and CeO 2 [21]; and surface vacancy induced magnetism in NiO [22]. Thus, these studies reveal that defects in the form of vacancies are the source of this behavior [11][12][13][14][15][16][17][18][19][20][21][22], however, sustainability of this magnetism up to long-range order requires exigency of the mechanism of interaction among these sources. It was observed that this kind of magnetism is governed by the double exchange mechanism through p-p interactions in Mg-doped SnO 2 [23], as well as B-, C-, and N-doped BeO systems [24].…”
Section: Introductionmentioning
confidence: 95%
“…To date, this magnetism is observed in a variety of materials with different sources of origin and is classified accordingly [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier civilizations relied on this force to create devices such as compasses [2]. Magnetism is now broadly studied in many realms and with many materials, particularly with regard to practical applications [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%